(untitled) (The Conference Hub, 2025)
This thesis substantiates the role of joint ventures in the development of investment and export activities of our republic. Direct cooperation between enterprises is considered a form of direct economic relations. Its distinctive features include: such activities are carried out between enterprises without state intervention; efficient use of resources and economic potential based on cooperation; cooperation enhances the export potential of enterprises and increases foreign currency revenues; moreover, it is evaluated not only by the delivery of finished products to consumers, but also by the supply of components at a technical level.